Preoperative Risk Score (PreopScore) to Predict Overall Survival After Resection for Hepatocellular Carcinoma. - Endo, Yutaka (2023)
Background: This study aimed to develop a holistic risk score incorporating preoperative tumor, liver, nutritional, and inflammatory markers to predict overall survival (OS) after hepatectomy for hepatocellular carcinoma (HCC). Methods: Patients who underwent curative-intent surgery for HCC between 2000 and 2020 were identified using an international multi-institutional database. Preoperative predictors associated with OS were selected and a prognostic risk score model (PreopScore) was developed and validated using cross-validation. Results: A total of 1676 patients were included. On multivariable analysis, preoperative parameters associated with OS included α-feto protein (hazard ratio [HR]1.17, 95%CI 1.03-1.34), neutrophil-to-lymphocyte ratio (HR2.62, 95%CI 1.30-5.30), albumin (HR0.49, 95%CI 0.34-0.70), gamma-glutamyl transpeptidase (HR1.00, 95%CI 1.00-1.00), as well as vascular involvement (HR3.52, 95%CI 2.10-5.89) and tumor burden score (medium, HR3.49, 95%CI 1.62-7.58; high, HR3.21, 95%CI 1.40-7.35) on preoperative imaging. A weighted PreopScore was devised and made available online (https://yutaka-endo.shinyapps.io/PrepoScore_Shiny/). Patients with a PreopScore 0-2, 2-3.5, and >3.5 had incrementally worse 5-year OS of 85.8%, 70.7%, and 52.4%, respectively (p < 0.001). The c-index of the test and validation cohort were 0.75 and 0.71, respectively. The PreopScore outperformed individual parameters and previous HCC staging systems. Discussion: The PreopScore can be used as a better guide to preoperatively identify patients and individualize pre-/post-operative strategies.